PERANCANGAN APLIKASI EDUKASI PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) BERBASIS ANDROID - Yogi Pratama; Rinna Rachmatika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The rapid advancement of mobile computing technology has changed mobile devices from mobile phones to smartphones that already have a variety of applications in them. So that smartphone devices have become a primary need for users. Accidents can happen to anyone, anywhere and anytime. First aid measures can be taken to reduce the impact on the accident. So the researchers developed an accident first aid application (P3K) on smartphone devices. The first aid application has a main feature that contains tutorials on first aid actions in an accident as well as several additional features in the form of drug information, types of rescue techniques, and emergency number calls. With the creation of this article in order to help the community, especially Android-based smartphone users, in obtaining information on first aid actions in accidents (P3K).